The Effect of Service Quality and Price on Customer Satisfaction with Business Innovation as an Intervening Variable at Airah Undangan Printing - Raodatul Jannah; M. Ikhwan Mansury (Intensi: Jurnal Riset Manajemen, 2026)
The rapid development of the creative service industry requires business actors to provide optimal customer satisfaction amidst intense competition. Shifting trends have given rise to a business phenomenon where local printing customers are no longer satisfied merely with low rates or standard services without an element of novelty. This paper investigates this phenomenon by formulating a single research question: how does business innovation mediate the effect of service quality and price on customer satisfaction at Airah Undangan Printing? The novelty of this study lies in the introduction of business innovation as an intervening variable within the context of regional MSME-scale creative industries, aiming to address the inconsistency of previous research that predominantly examined the macro sector while ignoring the dynamics of visual novelty. This quantitative explanatory research uses primary data from a sample of 45 customers (purposive sampling), analyzed using the PLS-SEM method via SmartPLS software. Empirical results show that service quality does not have a significant effect; however, price flexibility is proven to strongly trigger the emergence of business innovation, which then successfully mediates the creation of customer satisfaction. In conclusion, business innovation operates as an absolutely essential strategic bridge to transform price advantages into sustainable satisfaction. These findings provide practical implications for the management of printing MSMEs to prioritize budgets on exploring design novelty and ordering technology, rather than simply competing through price cut.